2020
DOI: 10.1080/00223891.2020.1842429
|View full text |Cite
|
Sign up to set email alerts
|

Complexity and Cognitive Engagement in the Rorschach Task: An fMRI Study

Abstract: Recently, Ales et al. (2019) reported on an eye-tracking study showing that Complexity and other R-PAS variables located in the Engagement and Cognitive Processing domain are correlated with a proxy marker for cognitive effort and engagement. The goal of the current study was to test the robustness and validity of Ales et al.'s (2019) findings by inspecting fMRI data. We hypothesized that the greater the level of engagement and cognitive effort put in place by a Rorschach test-taker, the greater the engagement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 41 publications
0
16
0
1
Order By: Relevance
“…As this parameter (fixations number) is a well-established proxy marker of cognitive engagement in the eye-tracking literature (e.g., Chen & Proctor, 2017;Jarodzka et al, 2010;Laeng et al, 2011), Ales et al's study strongly corroborates the R-PAS approach to interpreting complexity scores. Also consistent with R-PAS interpretive guidelines, a recent fMRI study conducted by Vitolo et al (2020) found that delivering more complex as opposed to simpler Rorschach responses showed increased activity in the dorsal attention network (d = .43, p < .01), a brain pathway deemed to be responsible for goaldirected or top-down attentional processes (Corbetta & Shulman, 2002;Ptak, 2012;Vossel et al, 2014).…”
Section: This Studymentioning
confidence: 63%
See 1 more Smart Citation
“…As this parameter (fixations number) is a well-established proxy marker of cognitive engagement in the eye-tracking literature (e.g., Chen & Proctor, 2017;Jarodzka et al, 2010;Laeng et al, 2011), Ales et al's study strongly corroborates the R-PAS approach to interpreting complexity scores. Also consistent with R-PAS interpretive guidelines, a recent fMRI study conducted by Vitolo et al (2020) found that delivering more complex as opposed to simpler Rorschach responses showed increased activity in the dorsal attention network (d = .43, p < .01), a brain pathway deemed to be responsible for goaldirected or top-down attentional processes (Corbetta & Shulman, 2002;Ptak, 2012;Vossel et al, 2014).…”
Section: This Studymentioning
confidence: 63%
“…In particular, Mihura et al's (2013) meta-analytic examination of all interpreted variables included in the popular comprehensive system (CS; Exner, 2003) led to the conclusion that 26 of them demonstrated excellent (r ≥ 0.33, p < .001, FSN > 50) or good (r ≥ .21, p < .05, FSN ≥ 10) validity, when using externally assessed criteria to evaluate them rather than self-report. 4 Moreover, during the past two decades, several Rorschach variables (e.g., human movement, complexity, Vista) have received extensive empirical validation using (a) neuroscientific techniques such as EEG (Ando' et al, 2018;Giromini et al, 2010;Pineda et al, 2011;Porcelli et al, 2013), fMRI (Asari et al, 2010;Giromini et al, 2017Giromini et al, , 2019aGiromini et al, , 2019bVitolo et al, 2020), and rTMS (Ando' et al, 2015(Ando' et al, , 2018, or (b) psychophysiological research methods involving the measurement of electrodermal activity (Giromini et al, 2016), eye movements (Ales et al, 2019;Minassian et al, 2005, Perry et al, 1995, 5-hydroxyindoleacetic acid (5-HIAA) (Lundbäck et al, 2006), and other physiological criteria (Meaney, 2011;Meyer et al, 2018).…”
Section: Rorschach Performance Assessment System (R-pas)mentioning
confidence: 99%
“…In the past decade, by utilizing the advancements of noninvasive neuroimaging techniques, researchers have explored neural mechanisms during Rorschach administration. The Rorschach cards were presented to healthy individuals while brain activity was measured using functional magnetic resonance imaging (fMRI; Asari et al, 2008; Giromini, Viglione, Pineda, et al, 2019; Mazhirina et al, 2020; Vitolo et al, 2020), electroencephalography (EEG; Giromini et al, 2010; Luciani et al, 2014), and near-infrared spectroscopy (NIRS; Hiraishi et al, 2012). One fMRI study focused on the human movement determinant (Giromini, Viglione, Pineda, et al, 2019), while another fMRI study focused on form quality (Asari et al, 2008), which provided helpful information about the interpretation of these response variables.…”
Section: Movement Determinantsmentioning
confidence: 99%
“…Most recently, the Complexity score has become the focus of their comprehensive research using the same dataset (Vitolo et al, 2020). The Complexity score is one of the most important scores in R-PAS.…”
Section: Movement Determinantsmentioning
confidence: 99%
“…Thus the authors' recommendation for event-related designs that employ one-off or brief exposure to stimuli, suited to unique stimuli, and those that require subjective interpretation such as spontaneous transitions in perception of an ambiguous visual stimulus (Kleinschmidt et al, 1998). Rather than averaged data, responses can post hoc be contrasted individually (Wagner et al, 1998) by statistical subtraction, or better, by statistical conjunction, which avoids the criteria for pure insertion, so that the neural correlates of two or more distinct task pairs are associated with common areas of activation and each share a common processing difference (Price & Friston, 1997). It allows for a factorial design such that the individual main effects of two or more variables can be calculated as well as the effect of one variable on another, for the observation of interactions (Friston et al, 1996) as is evident in the authors' work in social cognition.…”
mentioning
confidence: 99%